Daytime administration of melatonin has better protective effects on bone loss in ovariectomized rats - Li, Tian-lin; Liu, He-dong; Ren, Mao-xian; Zhou, Zhi; Jiang, Wen-kai; Yang, Min (Journal of orthopaedic surgery and research, 2023)
To explore the difference in the protective effects of intraperitoneal injection of exogenous melatonin of daytime or nighttime on bone loss in ovariectomized (OVX) rats. After bilateral ovariectomy and sham surgery, 40 rats were randomly divided into four groups: sham operation group (Sham), ovariectomy (OVX), and daytime melatonin injection group (OVX + DMLT, 9:00, 30 mg/kg/d) and nighttime injection of melatonin (OVX + NMLT, 22:00, 30 mg/kg/d). After 12 weeks of treatment, the rats were sacrificed. The distal femur, blood and femoral marrow cavity contents were saved. The rest of the samples were tested by Micro-CT, histology, biomechanics and molecular biology. Blood was used for bone metabolism marker measurements. CCK-8, ROS, and Cell apoptosis are performed using MC3E3-T1 cells. Compared with treatment at night, the bone mass of the OVX rats was significantly increased after the daytime administration. All microscopic parameters of trabecular bone increased, only Tb.Sp decreased. Histologically, the bone microarchitecture of the OVX + DMLT was also more dense than the bone microarchitecture of the OVX + LMLT. In the biomechanical experiment, the femur samples of the day treatment group were able to withstand greater loads and deformation. In molecular biology experiments, bone formation-related molecules increased, while bone resorption-related molecules decreased. After treatment with melatonin administration at night, the expression of MT-1β was significantly decreased. In cell experiments, the MC3E3-T1 cells treated with low-dose MLT had higher cell viability and greater efficiency in inhibiting ROS production than the MC3E3-T1 cells treated with high-dose MLT, which in turn more effectively inhibited apoptosis. Daytime administration of melatonin acquires better protective effects on bone loss than night in OVX rats.